Socialization Of Land Dispute Resolution Based On Agreements Between Parties In Serdang Bedagai Regency - Yulkarnaini Siregar; Yusuf Hanafi Pasaribu; Zetria Erma; Ismayani Ismayani; Taufika Hidayati; Jenda Ingan Mahuli; Widya Annisa (International Journal Of Community Service, 2025)
Land disputes are a complex problem that frequently occurs in Indonesia, including in Serdang Bedagai Regency. Land, as a strategic resource, is often the object of disputes due to unclear ownership, inheritance that is not properly resolved, land purchases that do not comply with legal procedures, and conflicts between communities and the government or companies in land acquisition. The problem faced by the people of Serdang Bedagai Regency is the lack of understanding of the mechanism for resolving land disputes through inter-party agreements as a more effective and efficient alternative to out-of-court settlement. Many land dispute cases drag on and end in social conflict due to the community's lack of understanding of the procedures and benefits of dispute resolution through agreements. To address this problem, socialization activities were conducted through counseling for the people of Pematang Kuala Village using presentations, group discussions, and interactive question and answer methods. The material presented included types of land disputes, settlement mechanisms through inter-party agreements, and their implementation and challenges. This activity was attended by residents experiencing land disputes, traditional leaders, village officials, and related stakeholders. This program is expected to increase public understanding about peaceful land dispute resolution, reduce the level of land conflict, and increase social harmony in Serdang Bedagai Regency.